Genetic Algorithms for Applied CAD Problems - Kureichik, Viktor M.; Malioukov, Sergey P.; Kureichik, Vladimir V.; Malioukov, Alexander S. (Studies in Computational Intelligence, 2009)
The development of intellectual systems connecting the human brain and computer technologies represents one of the most important problems of the 21st century. Therefore analytical methods of data mining of computer databases are being developed. Intellectual behavior of technical objects as well as the biological ones is defined by their structure, architecture and general organization first of all. Purposeful direction can be defined as intellectual behavior. It consists in finding the best ways to obtain some purpose by means of trial-and-error and study methods. These purposes are different for each category but all of them suppose the control object adaptation to unpredictable changes of their characteristics in time. The intellectual behavior of technical objects can be defined as simulation of some important functions of biological systems. New perspective technologies of genetic search and evolution simulation represent the kernel of this book. The authors wanted to show how these technologies are used for practical problems solution. This monograph is devoted to specialists of CAD, intellectual information technologies in science, biology, economics, sociology and others. It may be used by post-graduate students and students of specialties connected to the systems theory and system analysis methods, information science, optimization methods, operations investigation and solution-making. Chairman of the Applied Mathematics and Information Science Department of Power Engineering Institute, (Technical University), Moscow, Russia. Doctor of Science, Professor A. P. Eremeev.